More About When I's Meet: The Intergroup Ramifications of I-Sharing, Part II. (November 2018) - Pinel, Elizabeth C.; Long, Anson E.; Johnson, Leslie C.; Yawger, Geneva C.
Previous research on I-sharing (the belief that one has shared the same, in-the-moment subjective experience with another person) revealed its promise for improving intergroup relations. We expand on this research by (a) pursuing the mechanism underlying I-sharing's effects; (b) asking whether I-sharing promotes positive, behavioral intergroup outcomes; and (c) asking whether the effects of I-sharing generalize to the outgroup at large. Study 1 rules out the possibility that I-sharing promotes liking for an outgroup member via a process of subtyping. Study 2 shows that I-sharing promotes liking for an outgroup member because it promotes a general feeling of subjective connection to the I-sharer. Study 3 provides evidence that I-sharing promotes helping across intergroup lines, and Study 4 shows that I-sharing with one outgroup member reduces infrahumanization of the outgroup more generally. These four studies contribute to our growing understanding of the unique impact that I-sharing has on intergroup outcomes.